2009
DOI: 10.1523/jneurosci.5967-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Neural Signature of Lapsing Attention: Electrophysiological Signals Predict Errors up to 20 s before They Occur

Abstract: The extent to which changes in brain activity can foreshadow human error is uncertain yet has important theoretical and practical implications. The present study examined the temporal dynamics of electrocortical signals preceding a lapse of sustained attention. Twenty-one participants performed a continuous temporal expectancy task, which involved continuously monitoring a stream of regularly alternating patterned stimuli to detect a rarely occurring target stimulus whose duration was 40% longer. The stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
257
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(299 citation statements)
references
References 31 publications
34
257
8
Order By: Relevance
“…In Experiment 2, in contrast, the SART showed strong error speeding, which is consistent with previous literature (Mazaheri et al, 2009;O'Connell et al, 2009a). In a "dull" task such as the SART, subjects get into an automatic response mode, resulting in decreased reaction time, with lapses leading to fast errors (Robertson et al, 1997).…”
Section: Error-speeding and Posterror Slowingsupporting
confidence: 89%
See 2 more Smart Citations
“…In Experiment 2, in contrast, the SART showed strong error speeding, which is consistent with previous literature (Mazaheri et al, 2009;O'Connell et al, 2009a). In a "dull" task such as the SART, subjects get into an automatic response mode, resulting in decreased reaction time, with lapses leading to fast errors (Robertson et al, 1997).…”
Section: Error-speeding and Posterror Slowingsupporting
confidence: 89%
“…First, we showed that subtle manipulations of the Simon task [used to study response conflict (Leuthold, 2011)] resulted in varying degrees of theta and alpha oscillatory activity after errors. Second, we showed that errors in the SART [used to study attention lapses (Robertson et al, 1997)] resulted in comparable theta but stronger alpha error-related dynamics. Together, these findings demonstrate that errors may recruit, in varying degrees, different cooccurring neurocognitive processes.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous work has identified some behavioral and physiological measures that are modulated by mind wandering. These include behavioral measures such as response times (McVay & Kane, 2009), physical posture (Seli et al, 2014), prosody (Drummond & Litman, 2010), reading speed , and physiological measures such as brain activity (Christoff, Gordon, Smallwood, Smith, & Schooler, 2009;Mittner et al, 2014;O'Connell et al, 2009;Smallwood, Beach, Schooler, & Handy, 2008;Weissman, Roberts, Visscher, & Woldorff, 2006), peripheral physiological responses (Blanchard, Bixler, Joyce, & D'Mello, 2014;Pham & Wang, 2015;Smallwood et al, 2004), eye movements (Foulsham, Farley, & Kingstone, 2013;Frank, Nara, Zavagnin, Touron, & Kane, 2015;Reichle, Reineberg, & Schooler, 2010;Uzzaman & Joordens, 2011), eye blinks (Frank et al, 2015;Grandchamp, Braboszcz, & Delorme, 2014;Smilek et al, 2010;Uzzaman & Joordens, 2011), and pupil diameter (Franklin, Broadway, Mrazek, Smallwood, & Schooler, 2013;Smallwood et al, 2011).…”
Section: Abstract Mind Wandering Reading Eye Gaze Machine Learningmentioning
confidence: 99%
“…Because the frequent nontarget trials require constant responding, not-X CPTs enable investigation of RT patterns that precede and predict errors. For example, faster and more erratic correct responses have been shown to foreshadow errors within seconds (Cheyne, Carriere, & Smilek, 2006;Robertson et al, 1997), with neural markers of attention lapses preceding errors by up to 20 s (O'Connell et al, 2009). In these tasks, the most common errors are failures to inhibit response on target trials-that is, commission errors, which have been associated with reduced attention to task.…”
Section: Studies Of Vigilancementioning
confidence: 99%